2008
DOI: 10.1002/cne.21678
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic networks in the Ciona intestinalis larva

Abstract: Glutamate is a major neurotransmitter in the excitatory synapses of both vertebrate and invertebrate nervous systems and is involved in many neural processes including photo-, mechano-, and chemosensations, neural development, motor control, learning, and memory. We identified and characterized the gene (Ci-VGLUT) encoding a member of the vesicular glutamate transporter subfamily, a specific marker of glutamatergic neurons, in the ascidian Ciona intestinalis. The Ci-VGLUT gene is expressed in the adhesive orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(145 citation statements)
references
References 66 publications
10
135
0
Order By: Relevance
“…Glutamate is also one of the major neurotransmitters used in the vertebrate retina pathway, with the three VGLUTs being differentially expressed in specific classes of retina neurons [54]. Glutamate is further known to be present in the vestibular hair cells of different vertebrates [55-57] as well as in mechanosensory neurons of invertebrates [58]. In C. intestinalis , one VGLUT gene has been identified, which is expressed in both the central and the peripheral nervous system (Figure 13) [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamate is also one of the major neurotransmitters used in the vertebrate retina pathway, with the three VGLUTs being differentially expressed in specific classes of retina neurons [54]. Glutamate is further known to be present in the vestibular hair cells of different vertebrates [55-57] as well as in mechanosensory neurons of invertebrates [58]. In C. intestinalis , one VGLUT gene has been identified, which is expressed in both the central and the peripheral nervous system (Figure 13) [58].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is further known to be present in the vestibular hair cells of different vertebrates [55-57] as well as in mechanosensory neurons of invertebrates [58]. In C. intestinalis , one VGLUT gene has been identified, which is expressed in both the central and the peripheral nervous system (Figure 13) [58]. More specifically, VGLUT is found in sensory organs (photoreceptor cells of ocellus and otolith) and interneurons of the posterior sensory vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…In histological sections, the distribution of Ci-Syn transcripts in this area is characteristically uneven and probably labels specific subpopulations of neurons whose function is still to be investigated. Notably, in this area several types of chemically-identified neuronal types have been reported, including glutamatergic [69], cholinergic [43] and GABAergic neurons [35]. To account for the high number of neurons described in this region, neurons may be present also in Ci-Syn -negative areas.…”
Section: Discussionmentioning
confidence: 99%
“…These muscles contract in left/right alternation to produce the vigorous swimming behavior that aids in the dispersal of the larvae (Brown et al, 2005;Horie et al, 2010;Ohmori and Sasaki, 1977;Takamura et al, 2002). These neurons are thought to receive inputs from the sensory vesicle, as well as from the peripheral nervous system (Horie et al, 2008a;Takamura, 1998). It has been shown that swimming behavior is modulated by light and gravity (Horie et al, 2008b;Jiang et al, 2005;Tsuda et al, 2003), and that the response of the larvae to these stimuli can change over time (Kajiwara and Yoshida, 1985).…”
Section: Introductionmentioning
confidence: 99%